IDIOM DALAM BAHASA DAYAK BANJUR - Alin Alin; Laurensius Salem; Henny Sanulita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRACTAn idiom is an expression which does not follow the grammar of the related language. An idiom is a language expression in the form of words combination (phrases) which the meaning is united and cannot be interpreted by the meaning of the elements that make up it.This study was conducted to preserve Dayak Banjur language, especially its idiom. This study belongs to the linguistic field and focuses on the scope of the type, meaning, and function of idiom in Dayak Banjur language. The method of this study was Dayak Banjur language and folklore which contained the idiom which was told by the informant in Dusun Temedak Merat. Data collecting of this study used uninvolved conversation observation technique, involved conversation observation technique, fishing descriptive method, qualitative research form. The data source of this research was technique, interview, and recording. Based on the results of the study and data analysis can be concluded that there are 45 Dayak Banjur idioms which are gotten from interview and folklore. The types of the idiom divide into groups, they are: 36 full idioms, and 9 partial idioms.Key words: Dayak Banjur language, type, meaning, and the function of idiom.